IFNγ induces functional chemokine receptor expression in human mesangial cells - SCHWARZ, M (Blackwell Science Inc, 2002)
Infiltration of leucocyte populations into sites of inflammation is a common feature in renal diseases. Glomerular mesangial cells are potent producers of a variety of chemokines, leading to specific attraction of distinct types of inflammatory leucocytes into the glomerulus, but so far there is limited knowledge about the responsiveness of mesangial cells to chemokines. We investigated the expression of chemokine receptors and the responsiveness of primary human mesangial cells (HMC) to the chemokines which they produce, namely monocyte chemoattractant protein-1 (MCP-1) and interleukin (IL)-8. We found that mRNAs of the chemokine receptors CCR1, which has been shown before, CCR2 and CXCR2 were induced by T-helper cytokine interferon-gamma (IFNγ). In IFNγ-stimulated cells, CCR2 and CXCR2 were detectable by flow cytometry. Following treatment with IFNγ, HMC responded to MCP-1 and IL-8 with an increase of IL-6 mRNA and protein expression, which was in part blocked by pertussis toxin. Moreover, chemokine stimulation of transfected HMC led to an activation of the immunoregulatory transcription factors NFκB and AP-1. Additionally, we found that MCP-1 enhanced the expression of its own mRNA in cells activated to express CCR2, suggesting autocrine feedback mechanisms in MCP-1 regulation. Finally, IFNγ-activated cells migrated towards an MCP-1 gradient in a chemotaxis assay. These results strengthen the assumption that chemokines are not only involved in the recruitment of immune cells to inflamed tissues, but also seem to play a central role in the autocrine regulation of local tissue cells, leading to proceeding inflammation and possibly contributing to healing by mediating cell growth and migration.